2001
DOI: 10.1111/j.1365-2958.2001.02323.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous transposition in Aspergillus nidulans

Abstract: Aspergillus nidulans is one of the model ascomycete fungi. Transposition events have never been described in this organism. We have determined that this organism has at least 13 copies of a Fot1-related element. These copies are transcribed, non-methylated and polymorphic in various wild isolates. In spite of this, we have failed to isolate transposon insertions when the resident niaD gene is used as a transposon trap. This contrasts with the situation described previously in Fusarium oxysporum. We show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
44
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 47 publications
5
44
0
Order By: Relevance
“…Transposition of the LINE (Long Interspersed Nuclear Element: non-LTR retrotransposon) MGL (M. grisea LINE) was also observed in another experiment in which two M. grisea isolates from rice were crossed (Nishimura et al, 2000), and the Ds-like element, Ascot-1, has been shown to excise during mating in Ascobolus immersus b2 (Colot et al, 1998). No evidence of TE amplification was, however, found in crosses between A. nidulans strains (Li Destri Nicosia et al, 2001). These findings strongly suggest that the transposition of TEs may be enhanced during mating in fungi, but only some TE families are involved.…”
mentioning
confidence: 90%
“…Transposition of the LINE (Long Interspersed Nuclear Element: non-LTR retrotransposon) MGL (M. grisea LINE) was also observed in another experiment in which two M. grisea isolates from rice were crossed (Nishimura et al, 2000), and the Ds-like element, Ascot-1, has been shown to excise during mating in Ascobolus immersus b2 (Colot et al, 1998). No evidence of TE amplification was, however, found in crosses between A. nidulans strains (Li Destri Nicosia et al, 2001). These findings strongly suggest that the transposition of TEs may be enhanced during mating in fungi, but only some TE families are involved.…”
mentioning
confidence: 90%
“…The impala element belongs to the Tc1-mariner family (Daboussi et al, 1992;Daboussi, 1997). Impala has proved to be an efficient tool for gene-tagging and functional analysis, mainly because of its relatively high frequency (approximately 10 À5 ) of transposition and little host specificity within ascomycetes (Li Destri Nicosia et al, 2001;Villalba et al, 2001;Firon et al, 2003;de Queiroz and Daboussi, 2003;Carr et al, 2010;Cecchetto et al, 2004). However, impala also shows a trend for transposition within introns or 5 0 regions, rather than in ORFs or essential regulatory regions (Deschamps et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, in A. nidulans it was found that the heterologous transposons impala and Fot1 also show a marked tendency to integrate outside of ORFs (Li Destri Nicosia et al 2001). In this case it was suggested that this phenomenon is not based on target preferences of the transposon, but on a general 'immunity' of genes to foreign DNA.…”
Section: Discussionmentioning
confidence: 96%
“…In F. oxysporum the nitrate reductase gene from A. nidulans was first used as a transposon trap and the tagged gene then served in A. nidulans and F. monoliforme to monitor excision of the transposon. The reinsertion rate was estimated to range between 25% (for F. monoliforme) and 90% (for A. nidulans) (Hua- Li Destri Nicosia et al 2001). In contrast to these systems, the counterselectable plasmid system used for U. maydis does not allow us to calculate the frequency of excision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation